ANALISIS DIAGNOSTIK KESULITAN BELAJAR STATISTIKA MAHASISWA BKI PADA FAKULTAS USHULUDDIN ADAB DAN DAKWAH IAIN PALU - Karmawati Karmawati (ISTIQRA, 2016)
This study aims to know the students` learning difficulties of descriptive statistics; know the factors that cause learning difficulties of descriptive statistics BKI student at Ushuluddin Adab and Da`wah Faculty IAINPalu. This study uses descriptive quantitative approach with research subjects are BKI students at Ushuluddin Adab and Da`wah Faculty IAINPalu. Data collection techniques were used tests and interviews. The research instrument used is a diagnostic test and interview guidelines. Data analysis technique used is descriptive statistics. The results showed that students learning difficulties statistical average of 80.06% and in the category of "Very High." Factors that lead to statistical students` learning difficulties students include factors which causes an error in the test work on the problems, internal factors and external factors. Identification of diagnostic test results indicate the kinds of mistakes made by students in doing a matter of descriptive statistics. Mistakes done by the students include: error reading and understanding about the purpose of 69.23% (high); error of understanding the concept of 68.09% (high); misapplication of the formula of 65.61% (high); fault for not writing a formula of 83.06% (very high); calculating error of 72.53% (high); fault for not writing process amounted to 31.79% (lower); error the final result of 71.91% (high); errors due to inaccuracy of 79.77% (high); and the blame for not answering the questions of 10.82% (very low)